The Effect of Discussion Method on Students’ Speaking Ability at the Second Grade of SMP N 6 Kota Jambi in Academic Year 2018/2019 - Citra Annisa; Wennyta Wennyta (Universitas Batanghari Jambi, 2020)
This research was done to find the Effect of Discussion Method of Students' Speaking Ability at Second Grade students at SMP N 6 Kota Jambi in Academic Year 2019/2020. The researcher used a quantitative method as the research methodology with a random sampling technique. The sample of this research was the second of social grade students' at SMP N 6 Kota Jambi. The instrument of this research was a discussion method. This study involved 70 students, as the object of the study and divided into two classes. Class VIII D concisting of 35 students' was assigned as the experiment class and class VIII B concisting of 35 students' was assigned as the control class. The data was collected by using speaking test. Students' speaking bility is effect after treatment discussion method which in proven with students' can speak in treatment process. The data are collected by using test, pre test and post test. Thus the alternative hypothesis is accepted, the value of t-test higher than the value of t-table (3,064 > 1,69). Based on the finding above, it can be concluded that discussion method has a significant Effect of students' Speaking Ability at the Second Grade Students of SMP N 6 Kota Jambi in Academic Year 2019/2020.Key Words: Discussion , Method, Speaking Ability.